2019
DOI: 10.12688/f1000research.18758.1
|View full text |Cite
|
Sign up to set email alerts
|

Brexanolone, a neurosteroid antidepressant, vindicates the GABAergic deficit hypothesis of depression and may foster resilience

Abstract: The GABAergic deficit hypothesis of depression states that a deficit of GABAergic transmission in defined neural circuits is causal for depression. Conversely, an enhancement of GABA transmission, including that triggered by selective serotonin reuptake inhibitors or ketamine, has antidepressant effects. Brexanolone, an intravenous formulation of the endogenous neurosteroid allopregnanolone, showed clinically significant antidepressant activity in postpartum depression. By allosterically enhancing GABAA recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 146 publications
(175 reference statements)
4
51
0
1
Order By: Relevance
“…The neurosteroid brexanolone allosterically enhances GABAA receptor function and has antidepressant and anxiolytic effects (Lüscher and Möhler, 2019). However, there is also recent evidence to suggest that GABA antagonism can be therapeutic for emotional disorders, in support of the hypothesis presented here that these disorders involve overinhibition in the PFC.…”
Section: Gaba Agonism or Antagonism?supporting
confidence: 67%
See 1 more Smart Citation
“…The neurosteroid brexanolone allosterically enhances GABAA receptor function and has antidepressant and anxiolytic effects (Lüscher and Möhler, 2019). However, there is also recent evidence to suggest that GABA antagonism can be therapeutic for emotional disorders, in support of the hypothesis presented here that these disorders involve overinhibition in the PFC.…”
Section: Gaba Agonism or Antagonism?supporting
confidence: 67%
“…Most studies support the conclusion that glutamatergic activity in the PFC is reduced by chronic stress (Popoli et al, 2011;Musazzi et al, 2015). On the inhibitory side, the GABAergic deficit hypothesis (Lüscher et al, 2011;Lüscher and Möhler, 2019) is prevalent but has been challenged by others suggesting increased inhibitory neurotransmission in the PFC following chronic stress (McKlveen et al, 2016). Our work also challenged the GABAergic deficit hypothesis of stress and emotional dysfunction when we discovered that chronic stress increased the number of parvalbumin (PV) interneurons in the PFC, suggesting increased activity of this inhibitory cell population (Shepard et al, 2016;Shepard and Coutellier, 2018).…”
Section: Kv3mentioning
confidence: 79%
“…Our data showed that these DEGs were mainly enriched in the neurotrophin signaling pathway, insulin signaling pathway, alcoholism, GABAergic synapse, glutamatergic synapse, amphetamine addiction, MAPK signaling pathway, PI3K‐Akt signaling pathway and circadian rhythm (Table ). Interestingly, these signaling pathways are involved in the pathophysiology and treatment of depression . For example, GABA and glutamate neurotransmitter deficits are used to explain the neurobiological abnormalities associated with MDD, which has been well‐accepted .…”
Section: Discussionmentioning
confidence: 99%
“…Mice in which the production of specific subunits of the GABA receptors was blocked or reduced through genetic manipulation have been observed to exhibit depression-like behaviours, as well as physiopathological features which are typical of animal models of MDD. Overall, these findings indicate that alterations in GABA neurotransmission could play a role in the development of MDD by inducing a disruption of the stress response system [52,53].…”
Section: Subsequent Hypotheses: the Neurodevelopmental Glutamatergicmentioning
confidence: 72%
“…This association makes mGlu5 receptors an attractive target for indirectly modulating NMDA receptor function, and different compounds acting as negative modulators of mGlu5 receptors demonstrated an antidepressant-like activity in animal models [144]. Concerning the GABAergic system, emerging evidence indicates that drugs enhancing the function of specific GABA receptors exert an antidepressant action, thereby supporting the GABAergic deficit hypothesis of depression [52].…”
Section: Nmda Glutamatergic Receptor Blockers and Other Glutamatergicmentioning
confidence: 99%